Exploring Speech Acts on Get to Know by English Academy Videos of Ruangguru YouTube Channel - Arina Vionarsih; Otong Setiawan Djuharie (Fakultas Sastra, Universitas Muslim Indonesia, 2026)
The rapid development of information technology in Indonesia has fostered the growing use of digital platforms in language learning, particularly YouTube as a contextual and easily accessible audiovisual medium. This study aims to identify and analyze the types of speech acts, based on Searle's classification, in the